Análise do processo de gestão da inovação na construção civil: um modelo para o Ceará - Matos, Paulo Marcelo Albuquerque (2013)
The construction industry is recognized as an essential element that the Brazilian development demands for. All its importance is due to the power to provide the necessary infrastructure for several sectors of the economy. However, this sector still reveals its limited ability to drive its projects satisfactorily responding to the essential tripod: time, cost and quality. In order to change this situation, it is supposed to have not only isolated initiatives for innovation, but also a systematic innovation management process, which shall be able to modify its final products, processes and equipment. Based on the goals established in its strategies, companies can design the actions and procedures to form a clear, understandable and organized system, standardizations previously defined as well as evaluation metrics. Therefore, it is necessary that construction companies define opportunely the best way to achieve this level of management innovation, from a theoretically grounded model, adapted to their peculiarities and characteristics. Based on this, this research aims to identify the appropriate answer to the following research problem: Which model companies of Construction Industry Production Chain (CISC) could adopt to manage their innovation processes? This research aimed to fill the gap in knowledge generation and development of research in innovation in CISC. Its objective is to propose a management model of technological innovation for construction companies. Its theoretical foundation argues about the basic concepts of innovation, and then shows the innovation as a result of strategic management. It also brings a characterization of CISC and provides an overview of innovation management in the construction, in a Brazilian and international perspective. The last and main part of the theoretical framework addresses the management of the innovation process. This research will use the multiple case studies strategy, based on interviews and documental analysis, combined with direct and participant observation, based on model obtained from the theoretical foundations. The results revealed that the CISC surveyed companies have defined managing innovation processes, indicating the existence of specific tools and procedures, and thus influencing the final model proposed. Other factors were also important, as the presence of a leader/catalyst, the establishment of external alliances, the role of the internal network and the integration with the quality system.